Powiązania handlowe wewnątrz makroregionu Morza Bałtyckiego – w kierunku integracji regionalnej = Trade linkages within the Baltic Sea region – towards regional integration - Szejgiec-Kolenda, Barbara. Autor; Duma, Patryk. Autor (IGiPZ PAN, 2020)
Two events exerted an essential influence on the development of collaboration in the Baltic Sea Region (BSR) in the 21st century, namely: extension of the EU in 2004, due to which Baltic Sea became the inner sea of the EU (except for the Russian coast), and the elaboration and implementation in 2009 of the EU Strategy for the Baltic Sea Region, which established the framework for the contemporary deepening of cooperation among the Baltic states inside the EU structures. The initially adopted model of cooperation concentrated on the key environmental issues, to then get extended towards the policy domain, including the transborder policies (institutional cooperation), as well as transport and economic connections (Palmowski, 2017). The article, while following the stream of the current studies of the BSR as an economic region, tries to fill the gap of complexity and dynamism of development processes, concerning the scale and intensity of mutual economic relations in relation to BSR. Thus, the article presents the basic aspects, associated with the introduction of the macroregional strategies in the EU and a short description of the economic integration process of the BSR. Analysis is presented of the most important regularities regarding trade exchange between the countries of the BSR, with consideration of the quantitative changes (volume, dynamics), and of the structural ones (specialization of trade in goods and services), as well as the trade linkages at the local level, as seen from the perspective of Polish exports (case study). International comparisons are based primarily on the economic data on foreign trade in goods and in services. The analysis concentrates on the assessment of the transformations in the years 2011 2019 (for trade in services: 2011 2018), that is – already after the establishment of the Strategy and the period of recession, resulting from the global crisis of 2008. In the course of the recent years the changes in the trade linkages considered brought a significant increase in the volume of trade, both concerning goods and services (46.3%), which confirms the initial proposition of the deepening integration within the BSR. Yet, this process takes place in a spatially uneven manner, and it is significantly stronger for the trade in goods than for the services. Internal trade inside the region accounts for as much as 23.7% of the total trade of the BSR countries (this share for the EU countries amounting to 60.0%). Nowadays, the internal trade with the BSR countries is of the highest importance for the small economies of the Baltic states, which is partly due to their intermediate position between Western Europe and Eastern Europe (including, especially, Russia). The analysis of the spatial development of trade with the Nordic countries at the local level in Poland demonstrates the persistence of the applicability and popularity of the gravity models in the study of regula ities, associated with the development of export relations; for the local economies the distance to the sales market and the local economic base are the essential factors, differentiating the magnitude and the significance of exports, in this case – to the Nordic countries. The macroregional Strategy might be treated as a new form of diversified integration within the EU, while the elaborated instruments of the policy and the strategy implementation process can be seen as the response to the need of the cohesion policy, dedicated to the particular areas of supranational dimensions (Gänzle & Kern, 2016). The BSR is strongly internally differentiated, this statement applying to economic, social and demographic aspects (Kubka, 2018). Moreover, it can be expected that the region will remain a heterogeneous area (Laaser & Schrader, 2002), also in terms of the regional trade patterns. Thereby, new questions arise, concerning the further process of economic integration and the specificity of cooperation in the framework of the BSR.
24 cm
Keywords: Baltic Sea region; macroregional strategies; foreign trade in goods; international trade in services; flows of goods and services